Jahresbericht 1979 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1980)
Snow, Michael ; Stezaker, John ; Gerz, Jochen ; Beuys, Joseph ; Gehr, Andreas ; Troller, Josephine ; von Matt, Hans ; Ineichen, Irma ; Odermatt, Josef Maria ; Schaerer, Hans ; Buthe, Michael ; etc.
Duits
boek